Integrating Productive Zakat and Women's Empowerment to Achieve Sustainable Development Goals: A Path to Social Welfare and Economic Inclusion - Zunaidi, Arif; Maghfiroh, Fachrial Lailatul; Mushlihin, Imam Annas; Natalina, Sri Anugrah (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
This study aims to examine the role of integration of productive zakat and women's empowerment in achieving the Sustainable Development Goals (SDGs), focusing on the Kampung Zakat of Besole Village, fostered by BAZNAS Tulungagung Regency. Productive zakat, which is used as business capital for beneficiaries, combined with women's empowerment programs, aims to improve social welfare and economic inclusion. The research method uses a qualitative approach, with data collection through in-depth interviews, observations, and document analysis. The results of the study indicate that the integration of productive zakat and women's empowerment has a significant impact on increasing family income, access to education, and women's participation in local economic activities. In addition, this program also supports poverty reduction and gender inequality, which are part of the SDG targets. These findings emphasize the importance of productive zakat as an Islamic financial instrument that can contribute directly to sustainable development, especially in the context of women's empowerment in rural areas.